Peran Guru Penggerak dalam Kurikulum Merdeka Belajar - Ayu Reza Ningrum; Yani Suryani (AR-RIAYAH : Jurnal Pendidikan Dasar, 2022)
Pioneer teachers and the independent learning curriculum are one of the new breakthroughs that are created to develop the educational aspects by implementing technology 5.0 based on the direction of the Indonesian Minister of Education. This article aims to present data regarding the role of the pioneer teacher in the independent learning curriculum. This study applied qualitative research in a type of literary study. It means that the author examines published articles that convey the research results about pioneer teachers and independent learning curriculum. The discussion presented includes the understanding of the pioneer teachers, the role of the pioneer teachers, the meaning of independent learning and the implementation of the independent learning curriculum. The research results were expected to be used as a study or information that can be used as a theoretical basis for further research in the discussion of pioneer teachers in the independent learning curriculum as well as to optimize learning success applying technology-based learning 5.0.